First year real life experience with tenofovir alafenamide fumarate: The pythagorean cohort - Karasahin, Omer; Kalkan, Irem Akdemir; Dal, Tuba; Toplu, Sibel Altunisik; Harputluoglu, Murat; Mete, Ayse Ozlem; Celen, Mustafa Kemal (Kare Publ, 2023)
Background and Aim: In chronic hepatitis B infection, antiviral therapy significantly reduces the incidence of complications. This study aimed to present real-life 12-month effectiveness and safety data for TAF.Materials and Methods: This Pythagoras Retrospective Cohort Study included patients from 14 centers in Turkiye. The study presents 12-month results of 480 patients treated with TAF as initial therapy or after switching from another antiviral drug.Results: The study shows treatment of about 78.1% patients with at least one antiviral agent (90.6% tenofovir disoproxil [TDF]). The rate of undetectable HBV DNA increased in both treatment-experienced and naive patients. In TDF-experienced patients, the rate of alanine transaminase (ALT) normalization increased slightly (1.6%) within 12 months, but the change was not statistically significant (p=0.766). Younger age, low albumin, and high body mass index and cholesterol were identified as risk factors for abnormal ALT after 12 months, but no linear relationship was detected. In TDF-experienced patients, renal and bone function indicators showed significant improvement three months after the transition to TAF and remained stable for 12 months.Conclusion: Real-life data demonstrated effective virological and biochemical responses with TAF therapy. After switching to TAF treatment, gains in kidney and bone functions were achieved in the early period.
Keywords: Hepatitis B; real life; tenofovir alafenamide